In-Person and Remote Participation Review at IETF: Collaborating Without Borders - Andrade, Lucas; Braga, Juliao; Pereira, Stefany; Roque, Rafael; Santos, Marcelo (Anais do Workshop Pré-IETF (WPIETF), 2018)
The IETF has been acting as one of the main actors when discussing standardization of protocols and good practices on the Internet. Collaborating with the IETF community can be complex and distant for many researchers and industry members because of the financial aspect to travel to the meeting. However, it notes the collaboration between industry and academia is actively and progressively developing and refining standards within the IETF. One of the incentives for the increased participation in IETF meetings is because it is being transmitted in real time since 2015, allowing for voice and chat interaction of remote participants. Thus, in this paper, we have as objectives to give a brief vision about how to collaborate with the IETF and to analyze the importance of this new form of participation of the face-to-face meetings that has been growing in recent years.